ANALISIS PENGARUH CAR, NIM, BOPO, LDR, GWM TERHADAP PERUBAHAN LABA (Studi Pada Bank Pembangunan Daerah Di Indonesia Periode 2005-2007) - Setyarini, Adhista (JURNAL BISNIS STRATEGI, 2010)
This research is performed on order to test the influence of the variable Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), Biaya Operasional/Pendapatan Operasional (BOPO), Loan to Deposit Ratio (LDR), dan Giro Wajib Minimum (GWM) toward Earning Changes.Methodology research as the sample used purposive sampling, sample was accured 26 Bank Pembangunan Daerah in Indonesia. Data analysis with multi liniear regression of ordinary least square and hypotheses test used t-statistic and F-statistic at level of significance 5%, a clasic assumption examination which consist of data normality test, multicolinearity test, hetersoskedasticity test and autocorrelation test is also being done to test the hypotheses.During research period show as variabel and data research was normal distributed. Based on test, multicolinearity test, hetersoskedasticity test and autocorrelation test classic assumption deviation has no founded, this indicate that the available data has fulfill the condition to use multi linear regression model. This result of research show that variable BOPO and GWM did not influence Earning Changes. Variable CAR, NIM, and LDR positive significant influence toward Earning Changes. Prediction capability from these five variable toward Earning Changes is 20,6% where the balance 79,4% is affected to other factor which was not to be entered to research model.